Correlational Analysis: Knowledge, Training, and Attitude Towards First Aid Injuries Among Students of Astate Senior High School in Banjarmasin - Mira, Mira; Daud, Izma; Asih, Rinda Asmarani Nur (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Childhood injury is a growing public health concern that requires special attention. Students frequently participate in activities without considering the influence on their own body, resulting in injuries that can have a negative impact on their health and daily activities. The goal of this study was to assess the association between students' knowledge, training, and attitude toward first aid for injuries in a state senior high school in Banjarmasin. A correlational study design and a cross-sectional approach were utilized in this investigation. Data was obtained from a total of 1280 respondents, and a sample of 114 respondents was analyzed using a basic random sampling technique with probability sampling, with Spearman's rho as the statistical test utilized. With a p value of 0.05, the results suggest that there is a relationship between the level of knowledge, training, and attitude and the level of accuracy in first aid. It can be concluded that understudies' knowledge, training, and state of mind influence the precision of giving first aid for injuries, so it is critical for understudies to have positive knowledge, preparation, and demeanor in giving first aid to avoid mistakes that can lead to crises. Keywords: Attitude, First Aid for Injuries, Level of Knowledge, Training